MINIATUR TRAKTOR UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK PADA MATA PELAJARAN ALAT DAN MESIN PERTANIAN KELAS X.A ATPH SMK NEGERI SOPPENG - Lidya, Lidya; Caronge, Muhammad Wiharto; Nurmila, Nurmila (Jurnal Pendidikan Teknologi Pertanian, 2018)
This research is a classroom action research that aims to improve learning outcomes students on the subjects of tools and agricultural machines class X ATPH SMK Negeri 2 Soppeng with the use of tractorÂ  miniature media Subjects of this research are students of class XA ATPH SMK Negeri 2 Soppeng in the even semester of the academic year 2017 / 2018 consisting of 33 students. This research was conducted in two cycles consisting of four activities, namely: planning, implementation, observation, and reflection. Data collection of learning outcomes, and the learning activities of students are carried out using observation sheets and learning test results sheets in cycle I and cycle II. The collected data is analyzed quantitatively and qualitatively. Based on the research results, it can be concluded that the use of tractor miniature media can improve motivation and learning outcomes of students class X.A ATPH SMK Negeri 2 Soppeng.